442 Familial swyer syndrome associated with mixed germ cell tumor: a case report. (13th November 2020) - David, M; Castro, C
Abstract : Background: Swyer syndrome, a type of complete gonadal dysgenesis, is one of the rarer forms of the spectrum of disorders of sexual differentiation (DSD). Affected individuals have an XY karyotype but appear phenotypically female with characteristic hypoplastic gonads, presenting with primary amenorrhea and delayed puberty as main complaint. Only a few cases on siblings with Swyer syndrome have been reported. The accepted practice is to remove both gonads upon diagnosis to prevent the malignant transformation. Case: We present a case of a 14-year-old with primary amenorrhea and delayed puberty who consulted at our institution for an abdominopelvic mass. Family history is pertinent for relatives with menstrual abnormalities and delayed secondary sexual development; with an older sister having a confirmed XY karyotype. She underwent exploratory laparotomy to remove the tumor, however, the mass was deemed unresectable. The tumor was sampled and sent for frozen section which showed a malignant round cell tumor. Final histopathologic and immunohistochemistry studies showed a mixed germ cell tumor. She received three cycles of neoadjuvant chemotherapy prior to the definitive removal of the tumor and three more postoperatively. Chromosomal analysis confirmed an XY karyotype. Conclusion: Although rare, a diagnosis of Swyer syndrome must be considered in any adolescent with primary amenorrhea and an abdominopelvic mass. The diagnosis is confirmed with clinical findings combined with hormonal, gonadal, and chromosomal analyses. Routine gonadectomy and hormone replacement therapy are central to the management of patients with Swyer syndrome.